A shining lamp : the oral instructions of Catherine McAuley - McAuley, Catherine, 1778-1841 (Catholic University of America Press, 2017)
Catherine McAuley (1778-1841), the founder of the Sisters of Mercy in 1831, frequently gave oral instructions to the first Mercy community. Though she sometimes spoke explicitly about their religious vows, her words were always focused on the life, example, teachings, and evangelic spirit of Jesus Christ, emphasizing "resemblance" to him and fidelity to the calls of the Gospel. Her instructions have, therefore, a broad present-day relevance that can be inspiring and encouraging for all Christians. They are the "shining" words of a companion, a soul-friend, who offers guiding light to those who wend their pilgrim way toward the full embrace of God's merciful reign